1988
DOI: 10.1055/s-2006-962578
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins fromHypericum perforatum: Effects on Isolated Pig Coronary Arteries

Abstract: Various Croton species yielded a number of diterpenes which have been found to possess antiulcer (1), anticancer (2), and co-carcinogenic properties (3). Our investigation of Crown megalocarpus, collected from the Chiromo campus of the University of Nairobi, has yielded among other compounds, a novel diterpene belonging to the rare clerodane-type compounds possessing a 9,1O-abeo-CH3 group (1) (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…A number of studies refer to the composition of the essential oil (EO) of HP [10][11][12][13][14][15][16]. Typical HP EO constituents for the material collected in southern Europe (France, Italy, Turkey and Serbia) include the monoterpenes α-and β-pinene, limonene and myrcene, the sesquiterpenes trans-(E)-caryophyllene and caryophyllene oxide [17][18][19][20] and hydrocarbons such as n-decane, C 16 and C 29 alkanes and C 24 , C 26 and C 28 -alkanols [21]. Hypericum species are generally classed as essential oil-poor plants (oil yield <1.00 %, w/w) [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies refer to the composition of the essential oil (EO) of HP [10][11][12][13][14][15][16]. Typical HP EO constituents for the material collected in southern Europe (France, Italy, Turkey and Serbia) include the monoterpenes α-and β-pinene, limonene and myrcene, the sesquiterpenes trans-(E)-caryophyllene and caryophyllene oxide [17][18][19][20] and hydrocarbons such as n-decane, C 16 and C 29 alkanes and C 24 , C 26 and C 28 -alkanols [21]. Hypericum species are generally classed as essential oil-poor plants (oil yield <1.00 %, w/w) [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Even though a number of studies have been conducted to understand the mechanism of HP treatment on various disease conditions (Albert et al, 2002;Tedeschi et al, 2003;De Paola et al, 2005;Genovese et al, 2006a,b;Hammer et al, 2007;Saad et al, 2008;Dost et al, 2009;Cirak et al, 2010;Kraus et al, 2010;Samadi et al, 2010) only a few of them have reported the effect of HP on contractility of vascular system (Melzer et al, 1991;Apaydin et al, 2001;Gilani et al, 2005;Khan et al, 2009Khan et al, , 2010, however, there are no scientific reports with HP detailing its modulatory effects on the vascular tone. Hence, this study has investigated the vascular effects of HP at both smooth muscle and endothelial level.…”
Section: Discussionmentioning
confidence: 99%
“…Our present finding that HP decreases Phe contraction is in agreement with previous results (Apaydin et al, 2001;Khan et al, 2009), suggesting that changes in the calcium homeostasis of the cell is responsible for the vascular responsiveness to HP. Additionally, Melzer et al (1991) studied procanidin fractions of HP on isolated coronary arteries and reported that they prevent histamine and prostaglandin F2-α induced arterial contractions possibly through the inhibition of cellular phosphodiesterase (Gilani et al, 2005) that leads to the accumulation of muscle relaxant cyclic AMP, hence calcium sensitivity of the contractile elements is decreased (Karaki et al, 1997;Khan et al, 2010). High potassium induces contractions through the opening of voltage-dependent calcium channels (Karaki et al, 1997) and this phenomenon is assessed in this study as another good indicator of cellular calcium balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proanthocyanidins represent approximately 12% of dried weight of aerial biomass including the seeds [56]. The proanthocyanidin mixture contains only catechin (Fig.…”
Section: Proanthocyanidinsmentioning
confidence: 99%